SAMUEL BECKETT AND MONOLOGUE DRAMA: PERFORMING THE SELF - WOHL, Eugen Radu (Studia Universitatis Babeș-Bolyai Philologia, 2018)
Samuel Beckett and Monologue Drama: Performing the Self. The paper discusses four of Samuel Beckett’s monologue plays “Krapp’s Last Tape” (1958), “Play” (1964), “Breath” (1969), “Not I” (1972) and “A Piece of Monologue” (1979), with the purpose of delineating their structure and understanding the playwright’s experimental usage of this artistic genre, as well as its role within his overall dramatic corpus. We will attempt a historical and analytical foray into the many uses of the concept of monologue in both literature and theatre, with the intention to clarify its various appropriations in these fields and with the hope of eliciting further research into this important topic of analysis. Rezumat. Samuel Beckett și monologul teatral: Performarea sinelui. Lucrarea discută monologurile teatrale ale lui Samuel Beckett, “Ultima bandă a lui Krapp” (1958), “Joc” (1964), “Respirație” (1969), “Nu eu” (1972) și “Un fragment de monolog” (1979), cu scopul de a le delimita structura, modul unic prin care dramaturgul înțelege să se raporteze la acest gen dramatic, precum și rolul lor în ansamblul operei lui Beckett. Speranța noastră este ca aceast demers de cercetare a monologului, așa cum e înțeles în literatură și teatru, va reuși să stimuleze cercetări ulterioare asupra acestui subiect de analiză. Cuvinte cheie: Samuel Beckett, monolog dramatic, drama monologată, discurs fracturat, performance.